Coupling of cavitation with transverse waves through elastic solids - Rapet, Julien (Nanyang Technological University, 2020)
Cavitation is nowadays used for many medical applications, however the dynamics of cavitation in solids is not well understood. Liquids and solids can support the propagation of longitudinal / pressure waves. But thanks to their elasticity, solids can also transport transverse / shear waves. In this thesis, we present two discoveries involving coupling between cavitation and transverse waves through solids. We show the first evidences of the emission of shear waves during the collapse of laser induced bubbles in a soft solid and we described a non-yet reported novel mechanisms to generate cavitation from transverse waves in a thin liquid layer confined by two solid walls. Experimental and numerical methods are discussed, and models are proposed to explain the observed phenomena.